Severe upper gastrointestinal bleeding is halted by endoscopically delivered self-propelling thrombin powder: A porcine pilot study - Ali-Mohamad, Nabil; Cau, Massimo; Baylis, James; Zenova, Veronika; Semple, Hugh; Beckett, Andrew; McFadden, Andrew; Donnellan, Fergal; Kastrup, Christian (Endoscopy International Open, 2021)
Background and study aims Hemostatic powders have emerged recently to treat upper gastrointestinal bleeding (UGIB). Previously, we developed a novel self-propelling thrombin powder (SPTP) that effectively manages external pulsatile arterial bleed without compression, by effervescing and carrying thrombin into the wound. Here, we tested if SPTP, sprayed endoscopically, can manage severe UGIB in a live porcine model.Materials and methods Anesthetized pigs underwent laparotomy to insert the gastroepiploic vascular bundles into the stomach lumen via a gastrotomy. Bleeding was initiated endoscopically in the stomach by needle knife. SPTP was delivered to the site of bleeding from a CO2-powered spray device using a 7 FR catheter. Successful primary hemostasis, time to hemostasis, and the mass of SPTP delivered were measured.Results Hemostasis was achieved at all bleeding sites using SPTP. Mean time to hemostasis was 4.2 ± 0.9 minutes (mean ± standard error of the mean, n = 12). The average mass of SPTP delivered was 2.4 ± 0.6 g.Conclusions In this pilot study, SPTP successfully stopped 12 cases of severe UGIB, demonstrating early promise asa novel hemostatic powder.